Friction of ice during ice skating - Jansen, C. (Huygens-Kamerlingh Onnes Laboratory, Leiden University, 2017)
A hinge specifically designed for continuous friction measurements during ice skating was tested and used. The hinge can handle large vertical normal forces to simulate the weight of a real person on a skate, and is very flexible in the horizontal direction, so it deforms under a friction force. Two sensors on the hinge measure the deformation. Friction measurements were done with a part of a real skate, with varying temperatures, skating speeds and normal forces on the skate. A clear dependence of friction on temperature was found. Friction coefficients for an ice temperature of -20 C and air temperature of -10 C varied between 0.04 and 0.1, and coefficients for an ice temperature of -10 C and air temperature of -6 C varied from 0.006 to 0.016. The temperature of the skate was held at -10 C for both cases. The results also suggest friction dependence on skating speed and normal force, but this has to be verified. During the calibration of the setup it was found that the vertical force, controlled by air pressure, could be determined up to a factor of 2. Furthermore there was a large variation (up to a factor 2) in friction coefficients from measurements under the same circumstances, on the same ice layer. These could have been caused by changing humidity in the setup, as this was not monitored during the measurements. The setup works, but needs to be improved for more precise friction measurements. A humidity sensor in the setup is recommended.